Management of patellar instability in skeletally immature patients - Erdem Sahin; Reha Tandogan; Michael Liebensteiner; Guillaume Demey; Asim Kayaalp (EFORT Open Reviews, 2024)
Patellar instability is an important cause of knee disability in children and adolescents. A recent population-based study found an annual incidence rate of 2.58 per 100 000 individuals for lateral patella dislocations (LPD), with higher rates in females and patients aged <19. Two thirds of the injuries were related to sports (1). Higher annual rates up to 125 per 100 000 individuals have been found in smaller studies (2).